INVESTIGATING EMOTIONAL INTELLIGENCE IN PUBLIC AND PRIVATE INSTITUTIONS IN GHANA - Wasielewski, P. L (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
This study seeks to examine the nature of emotional intelligence among employees in public and private institutions in Ghana. A convenience sample of 140 respondents was used to collect data via a Likert Scale format questionnaire. Results indicated that the respondents had varying levels of emotional intelligence, with four dimensions identified as awareness of own emotions, management of emotions, awareness of others' emotions, and management of others' emotions. The study recommends that institutions incorporate the findings into their organizational strategies to ensure efficiency. This research contributes to the existing literature by exploring the nature of emotional intelligence in specific study areas, which has not been previously investigated. The study suggests that future research should investigate the role of demographic features in emotional intelligence. While the study may have external validity limitations due to its non-probability sample method, the results can provide information to management to optimize productivity and improve employee emotional levels.